Curriculum infusion of the social norms approach: information only vs. service learning. Issue 3 (2nd July 2016) - Flynn, Mark A.; Carter, Elizabeth
ABSTRACT: A two-group pretest–post-test quasi-experiment was conducted to analyze the impact of curriculum infusion of the social norms approach on students' alcohol perceptions and behaviors. This study extended previous research by examining two types of curriculum infusion, information only (IO) and service learning (SL). Also, owing to variations in drinking behavior between women and men, sex differences in IO and SL were assessed. In support of previous research, curriculum infusion significantly reduced participants' misperceptions of campus alcohol use. There were no differences found between the IO and SL groups. However, further analysis revealed differences based on participants' sex. Men in the SL group significantly reduced their drinking behavior. Since men tend to drink more than women and because heavy drinkers are typically more resistant to alcohol interventions, the SL results have practical implications for instructional communication with this demographic.